Model‐Based Assessment of Alternative Study Designs in Pediatric Trials. Part II: Bayesian Approaches. (17th August 2016) - Smania, G; Baiardi, P; Ceci, A; Cella, M; Magni, P
Abstract : This study presents a pharmacokinetic‐pharmacodynamic based clinical trial simulation framework for evaluating the performance of a fixed‐sample Bayesian design (BD) and two alternative Bayesian sequential designs (BSDs) (i.e., a non‐hierarchical (NON‐H) and a semi‐hierarchical (SEMI‐H) one). Prior information was elicited from adult trials and weighted based on the expected similarity of response to treatment between the pediatric and adult populations. Study designs were evaluated in terms of: type I and II errors, sample size per arm (SS), trial duration (TD), and estimate precision. No substantial differences were observed between NON‐H and SEMI‐H. BSDs require, on average, smaller SS and TD compared to the BD, which, on the other hand, guarantees higher estimate precision. When large differences between children and adults are expected, BSDs can return very large SS. Bayesian approaches appear to outperform their frequentist counterparts in the design of pediatric trials even when little weight is given to prior information from adults.